2022
DOI: 10.1101/2022.04.03.486872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saving the Devils is in the details: Tasmanian Devil facial tumor disease can be eliminated with interventions

Abstract: Tasmanian Devils facial tumor disease is severely impacting the population of this wild animal. We developed a computational model of the population of Tasmanian Devils, and the change induced by DFTD. We use this model to test possible intervention strategies Tasmanian conservationists could do. We investigate bait drop vaccination programs, diseased animal removals programs, and evolution of natural immunity. We conclude that a combination of intervention strategies gives the most favorable outcome. An addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As Tasmania is an island state, targeting of devil facial tumours presents a potentially more tractable problem than rabies. This is supported by two independent analyses that recently suggested that an OBV could potentially eliminate DFTD from Tasmania (Lamp et al 2021;Drawert et al 2022). An OBV platform for DFT1 and DFT2 is in development (Flies et al 2020) but the success of an OBV will depend not only on the effectiveness of the vaccine but also the bait distribution system.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…As Tasmania is an island state, targeting of devil facial tumours presents a potentially more tractable problem than rabies. This is supported by two independent analyses that recently suggested that an OBV could potentially eliminate DFTD from Tasmania (Lamp et al 2021;Drawert et al 2022). An OBV platform for DFT1 and DFT2 is in development (Flies et al 2020) but the success of an OBV will depend not only on the effectiveness of the vaccine but also the bait distribution system.…”
Section: Introductionmentioning
confidence: 59%
“…This is supported by two independent analyses that recently suggested that an OBV could potentially eliminate DFTD from Tasmania (Lamp et al . 2021; Drawert et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the growing adoption of cuttingedge technology like internet telephony and video conferencing has given businesses and society a number of chances to reduce commuting, hence reducing emissions. Additionally, growing e-banking and e-commerce usage is enabling internet transactions, which reduces need for physical transportation and thus lowers greenhouse gas emissions (Drawert et al, 2022). ICT is assisting in the provision of intelligent automated solutions in a number of areas, including electricity production, agriculture, and industry, in addition to reducing dependence on physical travel.…”
Section: Introductionmentioning
confidence: 99%
“…The Tasmanian devil population has declined by 80% since the discovery of DFTD (Woods et al 2020). This decline has led to changes in the species' ecosystem as feral cat populations have increased and quoll populations have decreased (Drawert et al 2022). However, contrary to predictions, local extinction of devils has not occurred (Farquharson et al 2022), and a natural immune response has been observed in some individuals (Woods et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020). This decline has led to changes in the species’ ecosystem as feral cat populations have increased and quoll populations have decreased (Drawert et al . 2022).…”
Section: Introductionmentioning
confidence: 99%